2016
DOI: 10.1039/c6ra09074e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing thermal transport efficiency in carbon composites using nanospacers

Abstract: Improved thermal transport efficiency of carbon-based composites has been achieved by inserting metallic spacers within the temperature range of 50-150 C. Al 2 O 3 , Ni, and SnO nano-particles are used as nanospacers in the graphite-like thin films, forming well-developed carbon framework. The composites show 42.5-57.7% increase in thermal conductivity (k), as compared with the pristine carbon. Among all the samples Al-inserted carbon composites exhibited the highest k value of 1128 W m À1 K À1 at 50 C.The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…This finding reveals that the efficiency of thermal transport of heat sinks depends not only on the intrinsic thermal properties (e.g., intrinsic k value), but also on the physical and mechanical preparation method (e.g., compressive treatment). Using the same test platform, the GN-G2 sample was found to possess higher k value than the other designs of heat sinks such as CNT/GN hybrid (1991 W/m K at 323 K) [2] and Al 2 O 3 -coated graphite (1128 W/m K at 323 K) [3]. It can be concluded that the selection of carbon materials is the major contributor to the thermal conduction.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This finding reveals that the efficiency of thermal transport of heat sinks depends not only on the intrinsic thermal properties (e.g., intrinsic k value), but also on the physical and mechanical preparation method (e.g., compressive treatment). Using the same test platform, the GN-G2 sample was found to possess higher k value than the other designs of heat sinks such as CNT/GN hybrid (1991 W/m K at 323 K) [2] and Al 2 O 3 -coated graphite (1128 W/m K at 323 K) [3]. It can be concluded that the selection of carbon materials is the major contributor to the thermal conduction.…”
Section: Resultsmentioning
confidence: 89%
“…Both CNTs and GNs have been demonstrated to display high theoretical thermal conductivities (k), thus heralding beneficial applications in heat exchangers and thermal management systems. It is generally recognized that low-temperature operation and efficient heat dissipation are key factors in determining the lifetime and the speed in current electronic and photonic devices [1,3]. Industrially, the most commonly-used materials for heat sinks are still Al and Cu, which possess lower k values and higher true densities, as compared to carbonaceous materials.…”
Section: Introductionmentioning
confidence: 99%